Developement of ready reckoner to assess the impact of excessive bark consumption in S/2d2 and S/2d3 harvesting systems - Silva T U K et al. (Journal of the Rubber Research Institute of Sri Lanka, 2012)
Recently, the poor bark management in different rubber plantations resulted in lower yield per tree in renewed barks leading to either maintaining at uneconomical levels or uprooting before full economic lifespan. Considering the long period,i.e. 24 years of harvesting latex from rubber plantation, monitoring bark consumption rates at very early stages are more effective and economical rather than implementing other special recommendations. However, the normal calculation to realize the excess rate of BC and the expected durations to be tapped according to the relevant ER is difficult to perform in the field. Therefore, attempts were made to prepare a Ready Reckoner to monitor the bark consumption of trees to identify the excess rate of the bark consumed for a certain period of tapping and the relevant durations to be finished for panel A,B,or C.
Keywords: Bark consumption; Calculation; Latex; Panel; Tapping